2022
DOI: 10.3389/fsurg.2022.859205
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial Radiofrequency Ablation vs. Septal Myectomy in Patients With Hypertrophic Obstructive Cardiomyopathy: A Systematic Review and Meta-Analysis

Abstract: BackgroundSeptal myectomy (SM) has been the gold standard therapy for most patients with hypertrophic obstructive cardiomyopathy (HOCM). Endocardial radiofrequency ablation of septal hypertrophy (ERASH) is a novel treatment for septal reduction. We aimed to assess the efficacy and safety between two treatment strategies.MethodsWe searched PubMed, Web of Science, Cochrane Library, and Embase databases to identify relevant studies published up to March 2021. Random-effect models were used to calculate standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, its success relies on suitable septal arterial anatomy and has the risk of procedure-related atrioventricular conduction complications [ 17 ]. Radiofrequency (RF) ablation is a new method for septal reduction, which is both minimally invasive and independent of coronary anatomy and has been shown to be feasible in HOCM [ 18 , 19 ]. The CARTO sound technology in patients undergoing radiofrequency septal ablation defines the ablation target with previously unparalleled accuracy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its success relies on suitable septal arterial anatomy and has the risk of procedure-related atrioventricular conduction complications [ 17 ]. Radiofrequency (RF) ablation is a new method for septal reduction, which is both minimally invasive and independent of coronary anatomy and has been shown to be feasible in HOCM [ 18 , 19 ]. The CARTO sound technology in patients undergoing radiofrequency septal ablation defines the ablation target with previously unparalleled accuracy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although septal myectomy provides symptom relief, owing to massive trauma and long convalescence, older patients have a lower expectation of the surgical procedure [8,9]. Therefore, ablation is more suitable for older patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that TSM was associated with similar procedural success rates and long-term outcomes compared to traditional septal myectomy. TSM may be a suitable alternative for patients with MVO who are not candidates for traditional septal myectomy [ 21 ].…”
Section: Surgical Septal Myectomymentioning
confidence: 99%
“…The options for patients with drug-refractory symptoms, who had an obstructive LVOT, included surgical myectomy, ASA, and short atrioventricular delay pacing. The best treatment for LVOT obstruction is still debatable since there are not enough randomized trials that directly examine different medications for the ailment [ 17 - 21 ]. According to recent data, ASA and septal myectomy are not associated with changes in short- and long-term all-cause mortality, cardiovascular mortality, or sudden cardiac death.…”
Section: Alcohol Septal Ablationmentioning
confidence: 99%